Combined effects of lipase and Lactiplantibacillus plantarum 1‐24‐LJ on physicochemical property, microbial succession and volatile compounds formation in fermented fish product. (31st January 2023) - Zhang, Zuoli; Wu, Ruohan; Xu, Wenhuan; Cocolin, Luca; Liang, Huipeng; Ji, Chaofan; Zhang, Sufang; Chen, Yingxi; Lin, Xinping
Abstract: BACKGROUND: Studies have shown that either the addition of starter culture or enzyme can improve fermentation in fish or other products. However, little research has been carried out on the effects of coupling starter cultures with lipase on the microbial community and product quality. Suanzhayu is a Chinese fermented fish product that mainly relies on spontaneous fermentation, resulting in an unstable flavor and quality. The present study investigated the impact of lipase and Lactiplantibacillus plantarum 1‐24‐LJ on the quality of Suanzhayu . RESULTS: Inoculation decreased pH and 2‐thiobarbituric acid reactive substances (TBARS) values, and also helped the dominance of the strain in the ecosystem, whereas lipase addition raised TBARS values and had little effect on pH, water activity ( a w ) and microbiota. The addition of lipase and/or Lpb. plantarum increased the content of alcohols, aldehydes, ketones, esters and umami amino acids. The co‐additions with the most significant effect and the total contents of volatile compounds (VCs) and free amino acids (FAAs) were 1801.92 g per 100 g and 21 357.05 mg per 100 g, respectively. Former‐ Lactobacillus was negatively correlated with pH, a w and Prevotella, but positively with VCs (ethyl ester of heptanoic acid, ethyl ester of octanoic acid) and FAAs (Tyr, Phe). Furthermore, adding Lpb. plantarum 1‐24‐LJ alone or in combination with lipase shortened the fermentation process. CONCLUSION: The present study provides a recommended Suanzhayu process approach for improving product quality and flavor, as well as shortening fermentation time, by adding Lpb. plantarum 1‐24‐LJ with or without lipase. © 2023 Society of Chemical Industry.